HAK PREFEREN ATAS PENAGIHAN UTANG PAJAK DALAM PERSPEKTIF HUKUM EKONOMI SYARI’AH - Haryati, Haryati; Rochmiatun, Siti; Afriansyah, Syafran (Program Studi Muamalah Fakultas Syariah dan Hukum, 2019)
ABSTRACT This thesis departs from academic anxiety when Taxpayers have tax debt which is a debt to the state. In tax law, the state has a special position, namely preferential rights (formerly) to collection of tax debts compared to personal debt. Preferred rights owned by the state must take precedence when the Taxpayer has a debt between tax debt and other preferred creditors. If the preferential rights of other preferred creditors are impaired because of the country's preferential rights, then the losses suffered by the community will outweigh the benefits. This study aims to answer about how the position of the country's preferential rights on tax debt collection and how the position of the country's preferential rights to collection of tax debt in the perspective of shari'ah economic law. This type of research is normative research (library research/ library research). The data collection technique used in this study is through literature studies. The type of data used is qualitative data. The data source used is secondary data. Data analysis in this study used a qualitative descriptive method. The results of this study conclude that the position of the country's preferential rights on tax debt collection has a prioritized position, which is more than the other preferred creditors. When a taxpayer has a creditor who has equal rights, the country's preferential rights to collection of tax debts are the most special because they have the facility to pay priority. In Shari'ah economic law, regarding the position of the state's preferential rights over the collection of tax debts, the payment takes precedence. The priority scale for the payment of the tax debt owned by the state takes precedence over payment of personal debt. This is because the results of the tax payments are used for the benefit of many people. Keywords: preferential rights, tax debt.